Do Underlying Asset, Duration, Default Risk Level, Sukuk Liquidity, and Profitability Affect Sukuk Yield? - Irawati, Dwi (AIBPM Publisher, 2024)
The purpose of this research is to determine how underlying assets, duration, default risk level, Sukuk liquidity, and profitability affect Sukuk yields between 2016 and 2019. One of the primary motivations for such studies was the failure of asset-based Sukuk with low default risk but not with asset-backed Sukuk. Then, this study focuses on two types of Sukuk, namely asset-based Sukuk and asset-backed Sukuk, and how the yield of each type is determined by the underlying asset. Until then, duration, default risk level, Sukuk liquidity, and profitability are used as control variables in evaluating the impact of underlying assets on Sukuk yields. This study employed an analysis of the difference between the two independent sample groups as well as multiple regression. The analysis was performed on each type of Sukuk. The analysis revealed that the Sukuk yields of the two groups differed, with an asset-based Sukuk generating more than an asset-backed Sukuk. Meanwhile, in asset-based Sukuk, the risk of default raises the yield while duration, liquidity, and profitability remain unchanged. The default risk level and profitability do not affect the yield in the asset-backed Sukuk group, whereas the duration and liquidity of the Sukuk have a positive effect on the yield.